Changes in psychomotor development in children with perinatal brain hypoxia - Igamova Saodat; Djurabekova Aziza; Bazarova Aziza (International Journal of Human Computing Studies, 2020)
The central nervous system is the main mechanism that determines the nature of the reactivity and adaptation of the body to a set of environmental factors. At the same time, autonomic imbalance acts as the root cause of the pathological process or as a predisposing factor, and it is advisable to use the cardiovascular system as an indicator of neurohumoral regulation its reactions are associated with the activity of the central nervous system, autonomic nervous system and subcortical centers.